Experimental characterization of the mechanical properties of railway wheels manufactured using class C material. (October 2016) - Zucarelli, T.; Moreira Filho, L.; Soares, H.; Vieira, M.; Reis, L.
Highlights: Mechanical properties of railway wheels manufactured using class C material. The results are in accordance with the microstructure and chemical composition. The mechanical testing results were satisfactory and comply standard AAR M-107. Decrease in strength with increasing temperature. Abstract: The railway system has an important role in developed countries: it is possible to see, nowadays, passenger trains crossing the Old Continent and achieving impressive speeds in the East; at the same time, cargo wagons are hitting load-by-axle records in North America. Railway wheels are a critical component to this system, as any failure can lead to derailment, potentially causing financial loss and/or fatal accidents. The present work aims to analyze the mechanical properties of forged wheels manufactured according to the American standard AAR class C, usually applied in freight cars due its chemical composition (around the eutectoid point) which achieves high mechanical resistance combined with moderated toughness. The mechanical tests to evaluate the mechanical strength, ductility, toughness and hardness were performed in accordance with the European standard BS EN 13262, as follows: tensile tests at different temperatures, impact tests, toughness tests and hardness Brinell tests. The obtained results are in accordance with the microstructure and chemical composition of class C material, and will be employed in future investigations for the numerical validation of the mechanical behavior for multiaxial fatigue conditions and development of new materials (micro alloyed steel).